Nature’s Voice: A Comparative Study of Eco-spiritualism in Vachanas and Gieve Patel’s ‘On Killing a Tree’ - Suvarna V. Patil (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Literary works are very powerful means to explore human relationships with nature. Literature attempts to rediscover the mystery and wonder of the world. Many poets and writers have tried to establish a meaningful relationship between literature and nature. Vachanas are such literary works written by Sharanas and Sharanes. For them, nature is a principal source of inspiration and spiritual enlightenment. They see nature as a living entity and believe that it is endowed with life, feeling, and purpose. Vachanas explore themes of spirituality, social reform, and human condition, often using nature imagery to convey deeper truths. For Vachanakaras, God prevails in every bit of nature. On the other hand, Gieve Patel’s poem On Killing a Tree vividly describes the process of killing a tree, highlighting the resilience of the tree and the cruelty of human actions. The powerful images and metaphors convey the violent act of man on nature and the severe consequences of such violent actions. A comparative study of these works explores the attitude of man towards nature, imagery, metaphor, and environmental messages. The paper also searches for a connection between nature and spirituality, emphasizing the sacredness of nature. The paper brings out the combination of ecological awareness with spiritual practices, promoting harmony with nature.